Pengaruh Celebrity endorser Terhadap Keputusan Pembelian Dengan kepercayaan merek Sebagai Variabel mediasi Pada Pelanggan Skincare Ms Glow Di Surabaya - Petronia Susanti Arni; Dewi Nuraini (Forum Kerjasama Pendidikan Tinggi, 2022)
This research is a type of quantitative research conducted on Ms Glow skincare products in the city of Surabaya. This study aims to determine whether or not the influence of celebrity endorsers on purcasing decisions through brand trust as a mediating variabel. The data collection method in this research is a questionneire or questionneire. The sampling technique used is the purposure sampling technique. The population that is the object of this research is Ms Glow Skin Care product customers with up to 100 respondents. Hypothesis testing with multilevel regresion analysis technique 1,2, and 3 with SPSS 21.0 program and sobel test for hypotehsis 4 with the help of the website. The results of this study indicate that the selebrity endorsers variable has a significant effect on brand trust in Ms Glow Skin Care products. The selebrity endorsers variable has a significant effect on purchasing decision on Ms Glow Skin Care products. And the selebrity endorsers variable has a significant effect on purchasing decisions through brand trust as a mediating variable.